Cooperação, confiança e interação: um estudo aplicado às corporações - Carvalho, Marinei Silva (Universidade do Vale do Rio dos Sinos, 2012)
This study deals with the concepts of cooperation and trust applied to corporations. The text begins by studying the dynamics of individual behavior in the collective, based on the theory of Raimo Tuomela, which divides cooperation in two basic modes of interaction: mode-me and mode-us. An important feature in his analysis is the mode-us interaction, since the interests of the group members are regulated by the condition of a cooperative exchange, making them abandon their individualistic characteristics and accept the social interactive features, allowing thus, the emergence of more refined levels of relationships. The second aspect will study cooperation in its natural bases. This aspect will be examined by a Darwinist point of view, cooperation being considered a social instinct that evolved through natural selection. The concept of trust will be presented along with morality, both deeply related with moral feelings, both occupying the role of sustaining cooperative interactions. Finally the final part of this study will analyze the dialogue between cooperation and trust with business organizations and their ethics, from an analysis of the dynamics of individuals (mode-me) inserted in the group (mode-us).
Keywords: Cooperação; Confiança; Evolução; Sentimentos morais; Ética empresaria; Cooperation; Trust; Evolution; Moral sentiments; Business ethics; ACCNPQ::Ciências Humanas::Filosofia